Income Drives Consumption, Not the Brain: Reassessing the Mediating Effect of Neurofinance in Urban Households - Septiani, Indri (Institut Bisnis dan Informatika Kesatuan, 2026)
Household consumption is a key indicator of economic well-being and is influenced by both income and behavioral financial factors. This study specifically examines the effect of household income on household consumption expenditure patterns in Makassar City, with neurofinance positioned as a mediating variable. A quantitative survey of 150 households was conducted, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that household income has a strong direct effect on consumption expenditure, while neurofinance has only a weak influence and does not significantly mediate the relationship between income and expenditure. These findings suggest that consumption patterns are predominantly driven by direct economic factors rather than behavioral financial mechanisms. Neurofinance appears to function more as a regulatory factor influencing consumption behavior rather than as an intermediary pathway. This study contributes empirically to the literature on household consumption by highlighting the contextual role of neurofinance and reinforcing the primacy of income in shaping expenditure decisions.